The success of a management information system in healthcare sector of Pakistan - Anwar Ujan, Imran; Suhaimi, Mohd Adam; Hydari, Manzar Abbas; Rind, Malook (2015)
Health informatics is the combination of different fields including information science, medicine and information technology for the sole purpose of formulating various systems to generate, validate, secure and integrate health-related data. The main purpose health informatics is to deliver an effective, integrated high quality health care system for patients. Health informatics bring together different, techniques, resources and systems for maximizing the usage of available wealth of technological advances, medical knowledge and drug breakthroughs. There has been a large scale usage of health informatics in a variety of health-related fields, including pharmacy, dentistry, nursing, public health and medical research clinical care This exploration is depict viewpoint on particular information and data utilizes by clients of a data game plan in one specific social insurance association. The administration data framework (MIS) is characterized as the data framework that gives administration data about budgetary and operational parts of clinic administration. The Pakistan Government Under the head of Health Affairs and Services, a total allocation of Rs 9,863 million has been made in the budget estimates 2013-14, which is higher by 25.7% and 24.9% respectively when compared with budget and revised estimates 2012-13. The allocation for hospital services forms the major component under this classification [12].